ANALISIS KESALAHAN SISWA KELAS VIII DALAM MENYELESAIKAN SOAL RELASI DAN FUNGSI - Rahmat, Agus; Bernard, Martin (IKIP Siliwangi, 2023)
This study is the background for errors in solving relationship and function problems. The study with the subject of class VIII students of State Junior High School 3 Cililin aims to describe the level of error carried out by students in solving relationship and function problems, the research methodology used in this study is a qualitative method with a descriptive approach, and the data produced in this study comes from the test results given to students with indicators of questions 1) Determining Relationships which are functions,Â 2) Applying the concepts of relationships and functions, 3) Determining the value of functions, 4) Finding the concept of function relations, 5) Defining relationships and functions. From these results, it was found that the average student error was at a moderate criterion of 65%.